2017
DOI: 10.1186/s12885-017-3591-z
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of E-cadherin and N-cadherin expression in Gliomas

Abstract: BackgroundEpithelial-mesenchymal transition (EMT), principally involving an E-cadherin to N-cadherin shift, linked to tumor invasion or metastasis, and therapeutic resistance in various human cancer. A growing body of recent evidence has supported the hypothesis that EMT play a crucial role in the invasive phenotype of gliomas. To evaluate the prognostic connotation of EMT traits in glioma, expression of E-cadherin and N-cadherin was explored in a large series of glioma patients in relation to patient survival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
54
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 32 publications
8
54
0
Order By: Relevance
“…Moreover, EMT mesenchymal markers N-cadherin and vimentin showed increased expression. N-cadherin and vimentin can loosen the tumor cells, resulting in migration and spread (17,18). The results of this study showed that E-cadherin expression was low in EOC tissues and highly expressed in adjacent tissues; Snail1, N-cadherin and vimentin were highly expressed in EOC tissues and the expression was low in adjacent tissues, which was consistent with related studies and the molecular biological characteristics of the EMT process of ovarian cancer.…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, EMT mesenchymal markers N-cadherin and vimentin showed increased expression. N-cadherin and vimentin can loosen the tumor cells, resulting in migration and spread (17,18). The results of this study showed that E-cadherin expression was low in EOC tissues and highly expressed in adjacent tissues; Snail1, N-cadherin and vimentin were highly expressed in EOC tissues and the expression was low in adjacent tissues, which was consistent with related studies and the molecular biological characteristics of the EMT process of ovarian cancer.…”
Section: Discussionsupporting
confidence: 89%
“…Because previously study showed that N-cadherin enhanced glioma migration and metastasis [20]. And Vimentin is a marker of cellular EMT, a phenomenon associated with GBM invasion and metastatic [21].…”
Section: Inhibit Igfbp5 Represses Gbm Cell Invasionmentioning
confidence: 98%
“…Recent advancements in the 3D bioprinting technologies have facilitated the construction of clinically relevant biomimetic tissues, which are able to replicate the delicate architecture and complex composition of different tissues and applied for the tissue regeneration. [11,12] Such models will allow to test drugs in a realistic environment before embarking on animal studies, eventually contributing to reducing and refining animal experiments. Due to this versatility, 3D bioprinting can be a promising tool to create 3D models that mimic the architecture and cellular composition of GBM, allowing us to better study the tumor biology as well as screen drugs in a relevant environment.…”
Section: Main Textmentioning
confidence: 99%
“…On the contrary, CDH1, which is significantly downregulated in glioblastoma cells in our model, does not show any significant difference in GBM patients indicating that other factors might influence the overall expression of this gene in patients, as a low CDH1 expression is characteristic for GBM as described elsewhere. [12,22] .…”
Section: (Supplementary Figure S4c and S4d)mentioning
confidence: 99%